Systematic Literature Review: Improving Students' Numeration Abilities With an Ethnomathematics Approach - Bela, Maria Editha; Marselina Wea; Melkior Wewe; Wilibaldus Bhoke (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to systematically examine how and under what conditions ethnomathematical approaches contribute to the development of students’ numeracy skills in mathematics education. Although ethnomathematics has been widely studied, there remains a lack of systematic synthesis focusing specifically on its impact on numeracy outcomes within diverse instructional contexts. This study adopts a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework to ensure methodological transparency and rigor. Relevant studies were identified from multiple academic databases, including Google Scholar, Semantic Scholar, Crossref, SINTA, and DOAJ, supported by the Publish or Perish tool. Through a structured selection process involving identification, screening, eligibility assessment, and inclusion, 20 peer-reviewed articles were analyzed based on predefined criteria. The findings reveal that ethnomathematical approaches can enhance students’ numeracy by embedding mathematical concepts within culturally meaningful contexts, thereby strengthening conceptual understanding and problem-solving abilities. However, the effectiveness of this approach is not uniform and is strongly influenced by instructional design, the authenticity of cultural integration, and teacher pedagogical competence. This study contributes to the field by clarifying the conditions under which ethnomathematics supports numeracy development and by offering a more nuanced understanding beyond general effectiveness claims. The findings provide a foundation for developing culturally responsive numeracy instruction and suggest directions for future research, particularly in terms of experimental validation and cross-contextual analysis.